INVESTMENT PROJECT ANALYSIS ON OIL PIPELINE REPLACEMENT PROJECT - Idham, Ali
The “Alfa” block is one of Indonesia’s largest crude oil producers. The crude oil from production fields is transported by pipelines to terminal tank facility. One of investment opportunity is the replacement of 10-inch existing aging pipeline to secure delivery of crude oil from BLM gathering station for the next 20 years to support national oil production. This final project assesses the financial analysis using gross split scheme to understand the economics of the proposed investment project as considerations for the next “Alfa” block operator prior to final investment decision. Discounted cash flow (DCF) method and sensitivity analysis are used as financial tools with specific profitability measures using IRR, NPV, PI, and Payback Period. This final project also perform cost risk assessment using Monte Carlo simulation as one of modern solutions to obtain probabilistic capital investment cost that fully reflect the impact of uncertainty and risk. The financial analysis results showing a positive NPV, high PI, short payback period and IRR more than company discount rate policy indicate that the investment project is feasible to be executed. The realistic and achievable capital investment budget can be set based on probabilistic cost resulted from the implementation of cost risk assessments.